Biodiversity of marine fungi in Malaysian mangroves - Alias, S.A.; Zainuddin, N.; Jones, E.B.G. (Walter De Gruyter & Co, 2010)
Senescent and decaying substrata were collected in selected Malaysian mangroves (prop roots, pneumatophores, overhanging branches and twigs of mangrove trees, driftwood) to study the diversity of marine mangrove fungi. One hundred and thirty-nine marine fungi were fully identified to specific level (115 Ascomycota, 2 Basidiomycota, 22 anamorphic taxa). Based on percentage of occurrence, the most common species were Lignincola laevis (16.8%), Verruculina enalia (13.3%), Trichocladium achrasporum (12.1%), Savoryella lignicola (11.8%), Dictyosporium pelagicum (11.2%), Halocyphina villosa (11.0%) and Lulworthia grandispora (10.9%). Among the samples, 84.2% supported an average number of 2.8 fungal species per sample. Of the 139 fungi identified in this study, circa 84% (117 species) are only found in the tropics/subtropics, mostly as mangrove species. Factors affecting the distribution and abundance of mangrove fungi are discussed, including: substrate specificity, sampling frequency and intensity, vertical distribution and geographical locations.